Enhancing students' algebraic numeracy through the development of a concrete algebra box: R&D study in Indonesian secondary education - Tali Wangge, Maria Carmelita; Bela, Maria Editha (Al-Jabar: Jurnal Pendidikan Matematika, 2025)
Purpose: This study aims to improve students’ algebraic numeracy by developing a concrete teaching aid “the Algebra Box” to facilitate learning of addition and subtraction operations involving algebraic expressions among Grade VII students in Indonesia. Method: Employing the Research and Development (R&D) approach, this study followed six key stages: identifying potential problems, data collection, product design, design validation, product revision, and final implementation. The participants were students from Grade VII at SMPN 2 Soa, Indonesia. Data were collected through classroom observation, learning assessments, and validation by subject teachers. Pre- and post-intervention assessments were conducted to measure learning outcomes before and after the implementation of the Algebra Box. Findings: The results reveal a significant improvement in students’ numeracy skills. Prior to the intervention, 20 percent of students scored in the high category. After implementing the Algebra Box in learning sessions, this increased to 80 percent. Students showed enhanced conceptual understanding, active participation, and improved problem-solving accuracy. The concrete nature of the Algebra Box helped bridge abstract algebraic concepts with tangible representations, thereby reinforcing cognitive engagement and learning retention. Significance: This study highlights the effectiveness of manipulative-based learning tools in transforming mathematics education, particularly in developing countries where abstract reasoning often poses a major challenge. The Algebra Box not only supports the transition from teacher-centered to student-centered learning but also fosters critical thinking and collaborative problem-solving among students. These findings support the integration of concrete instructional media into algebra curricula as a strategic method to improve learning outcomes and mathematical confidence in early secondary education.